Grammar and Vocabulary of the Lau Language, Solomon Islands - Ivens, W. G. (Walter George), 1871- (Salt Lake City, UT : Project Gutenberg, 2004)
"Grammar and Vocabulary of the Lau Language, Solomon Islands" by W. G. Ivens is a linguistic treatise written in the early 20th century. This scholarly work focuses on the Lau language, which is spoken by the residents of the artificial islets off the northeast coast of Big Malaita in the Solomon Islands. The author aims to meticulously document the grammar and vocabulary of this language, offering crucial insight into its features and usage. At the start of this publication, Ivens provides an overview of the Lau language's geographical context, highlighting its variants and the influences from neighboring languages like Sa'a and Fiu. He details the methods through which he acquired knowledge of Lau, emphasizing the importance of local interactions and educational influences. The beginning establishes the significance of understanding this language not only for linguistic purposes but also for appreciating the cultural identity it represents among the Lau-speaking communities. (This is an automatically generated summary.)
Release date is 2004-05-01
Produced by David Starner, with help from Charles Franks and the Distributed Online Proofreading Team
Keywords: Lau language